1984
DOI: 10.1677/joe.0.1000287
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pinealectomy on the plasma concentrations of prolactin, cortisol and testosterone in sheep in short and skeleton long photoperiods

Abstract: Two experiments were carried out to investigate the effects of pinealectomy on the responses of prolactin, cortisol and testosterone to skeleton long photoperiods (7 h light: 10 h darkness: 1 h light: 6 h darkness; 7L: 10D: 1L: 6D) compared with short photoperiods (8L: 16D) in lambs. The first experiment included 23 female Suffolk cross sheep aged 10 months, of which six were pinealectomized. The skeleton long photoperiod significantly increased plasma levels of prolactin but this was blocked by pinealectomy; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
4
11
0
Order By: Relevance
“…Several differences between the previous and present study can explain the discrepant results (strain and sex of animals, experimental procedures and conditions). In other ruminant species, seasonal or photoperiodic variation of cortisol levels has also been found in some but not all studies (Brinklow and Forbes, 1984;Bubenik and Brown, 1989;Bubenik et al, 1975;1977;1983;Feher et al, 1994;Ingram et al, 1999;Kennaway et al, 1981;Leining et al, 1980;Lincoln et al, 1982;Monfort et al, 1993). The variability of patterns has been suggested to depend, for example, on the age and sex of the animals or the social structure of the studied herd (Feher et al, 1994).…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Several differences between the previous and present study can explain the discrepant results (strain and sex of animals, experimental procedures and conditions). In other ruminant species, seasonal or photoperiodic variation of cortisol levels has also been found in some but not all studies (Brinklow and Forbes, 1984;Bubenik and Brown, 1989;Bubenik et al, 1975;1977;1983;Feher et al, 1994;Ingram et al, 1999;Kennaway et al, 1981;Leining et al, 1980;Lincoln et al, 1982;Monfort et al, 1993). The variability of patterns has been suggested to depend, for example, on the age and sex of the animals or the social structure of the studied herd (Feher et al, 1994).…”
Section: Discussionmentioning
confidence: 87%
“…Thus, some long-term seasonal variation in cortisol levels might be expected at least in natural conditions, the winter being the period of energy consumption and the summer the period of energy restoration. Indeed, there are studies that have demonstrated annual changes or photoperiodic modulations of glucocorticoid levels, whereas there are also studies which have failed to detect such alterations (Brinklow and Forbes, 1984;Bubenik and Brown, 1989;Bubenik et al, 1975;1977;1983;Feher et al, 1994;Ingram et al, 1999;Kennaway et al, 1981;Leining et al, 1980;Lincoln et al, 1982;Monfort et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In all data points, in both experimental conditions, serum cortisol concentrations were within the physiological range in horses (Kaneko et al 1997). Some authors have reported that cortisol concentrations are influenced by the duration of photoperiod such that long or progressively increasing photoperiods depress serum cortisol, and short or gradually decreasing photoperiods increase cortisol (Leining et al 1980;Brinklow and Forbes 1984). The rhythm did not change between L/D cycle and constant darkness.…”
Section: Discussionmentioning
confidence: 92%
“…we have confirmed our previous observation of a diurnal fhYthm in maternal and foetal plasma prolactin concentrations In the late pregnant ewe (1) and we have demonstrated that the maternal prolactin rhythm is present until at least 24 h before In the present study there was a rise in maternal prolactin associated with the time of lights off (at 1900 h) in both the intact and pineactomized groups. A number of studies in lambs and sheep have reported that there is a similar 'dusk onset' or 'lights off' peak in prolactin concentrations when the animals are maintained in long photoperiods (11,14,16,18,(20)(21)(22). The neuroendocrine control mechanisms underlying this daily increase in prolactin concentrations are poorly understood.…”
Section: Discussionmentioning
confidence: 99%